A Qualitative Analysis of Provider Barriers and Solutions to HIV Testing for Substance Users in a Small, Largely Rural Southern State. Issue 4 (25th March 2013) - Wright, Patricia B.; Curran, Geoffrey M.; Stewart, Katharine E.; Booth, Brenda M.
Abstract Purpose Integrating HIV testing programs into substance use treatment is a promising avenue to help increase access to HIV testing for rural drug users. Yet few outpatient substance abuse treatment facilities in the United States provide HIV testing. The purpose of this study was to identify barriers to incorporating HIV testing with substance use treatment from the perspectives of treatment and testing providers in Arkansas. Methods We used purposive sampling from state directories to recruit providers at state, organization, and individual levels to participate in this exploratory study. Using an interview guide, the first and second authors conducted semistructured individual interviews in each provider's office or by telephone. All interviews were recorded, transcribed verbatim, and entered into ATLAS.ti software (ATLAS.ti Scientific Software Development GmbH, Berlin, Germany). We used constant comparison and content analysis techniques to identify codes, categories, and primary patterns in the data. Findings The sample consisted of 28 providers throughout the state, 18 from the substance use system and 10 from the public/ community health system. We identified 7 categories of barriers: environmental constraints, policy constraints, funding constraints, organizational structure, limited inter‐ and intra‐agency communication, burden of responsibility, and client fragility. Conclusions This study presents the practice‐based realities of barriers to integrating HIV testing with substance use treatment in a small, largely rural state. Some system and/or organization leaders were either unaware of or not actively pursuing external funds available to them specifically for engaging substance users in HIV testing. However, funding does not address the system‐level need for coordination of resources and services at the state level.